2004
DOI: 10.1038/sj.bjc.6601845
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of thymidine phosphorylase by neoadjuvant chemotherapy in primary breast cancer

Abstract: The combination effect of docetaxel and capecitabine on tumour response rate and survival was demonstrated recently in metastatic breast cancer patients. This combination was based on an experimental hypothesis that taxane can increase tumour sensitivity to the effect of capecitabine through the upregulation of thymidine phosphorylase (TP), which is responsible for the metabolism of 5-fluorouracil (5-FU) and its derivatives, including capecitabine. To examine the alteration in TP expression before and after ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 25 publications
(16 reference statements)
2
26
1
Order By: Relevance
“…This is supported by clinical observations of a significant relationship between response to treatment with the combination of the taxane docetaxel and capecitabine and expression of TP in tumor tissue [5]. Also anthracyclines have been reported to enhance TP upregulation [6].…”
Section: Introductionsupporting
confidence: 67%
“…This is supported by clinical observations of a significant relationship between response to treatment with the combination of the taxane docetaxel and capecitabine and expression of TP in tumor tissue [5]. Also anthracyclines have been reported to enhance TP upregulation [6].…”
Section: Introductionsupporting
confidence: 67%
“…26 Meanwhile, preclinical studies suggested that TP was often up-regulated by stress such as hypoxia, radiation and chemotherapy agents, 27 which included anthracyclines, taxanes, cyclophosphamide, and platinum compounds. 28 Furthermore, given the synergistic effect between cisplatin and 5-FU, 12,13 it is reasonable to expect an enhanced activity of capecitabine when administered in combination with cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…TP is upregulated in tumors by receiving stress such as hypoxia, radiation and chemotherapeutic damage. Several types of cytokines such as interleukin-1, tumor necrosis factor-α, interferon-γ also upregulate the expression of TP in malignant cells (33). Endo et al have previously reported that several types of antitumor drugs, such as taxanes, cyclophosphamide and oxaliplatin, upregulated TP in tumor tissues and that capecitabine in combination with these TP upregulators showed synergistic antitumor activity in xenograft models (32).…”
Section: Discussionmentioning
confidence: 99%